High-strength polyurethane material for polishing pads and method for producing same
Patent Information
- Application Number
- CN202611162469.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]聚氨酯抛光垫是由聚氨酯聚合体经发泡、固化后制得,聚氨酯聚合体主要由软段和硬段构成,软段主要成分为聚酯/聚醚等多元醇,硬段则由异氰酸酯与扩链剂、交联剂等组成,通过调节聚氨酯聚合体中软段与硬段的材料种类与占比可以赋予聚氨酯抛光垫不同的性能,较高的硬段占比能够提高聚氨酯抛光垫的模量与硬度,抛光垫平坦化能力变强,但同时会导致硬段与软段相分离过度、硬段聚集粗化,会导致抛光垫断裂伸长率、韧性降低,进而造成晶圆表面产生划痕受损,较高的软段占比能够提高聚氨酯抛光垫的韧性,不易破坏晶圆,但是其模量、耐磨性不足,受压易发生蠕变形变,平坦化能力变弱,导致抛光效率降低
[0021]1.本发明以N-甲基单乙醇胺与碳酸二甲酯制备了扩链剂,其分子结构带有丰富的氨基甲酸酯基团,可以提高聚氨酯硬段的氢键密度与内聚强度,进而提升聚氨酯材料的拉伸强度、硬度与耐磨性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyurethane composite materials technology, specifically a high-strength polyurethane material for polishing pads and its preparation method. Background Technology
[0002] Chemical mechanical polishing (CMP) is a core technology in semiconductor wafer surface processing. Through the synergistic effect of chemical etching and mechanical abrasion, it achieves smooth planarization of wafers and substrates. In CMP, the polishing slurry is primarily responsible for chemical etching, while the polishing pad is primarily responsible for mechanical abrasion. The combination of these two components results in a highly planarized wafer surface, significantly reducing surface roughness and defects, thereby improving the accuracy of subsequent processing and the yield of the finished product. Therefore, the polishing pad is a crucial component of the CMP process, primarily serving to store the polishing slurry, transport it to the wafer processing area, remove waste, transfer processing loads, and ensure the smooth operation of the polishing process. Consequently, the polishing pad material must possess excellent corrosion resistance, good hydrophilicity, and mechanical properties. Currently, polyurethane polishing pads are the most common type, widely used in CMP processes due to their good chemical stability, wear resistance, and high polishing efficiency.
[0003] Polyurethane polishing pads are made from polyurethane polymers through foaming and curing. The polyurethane polymer mainly consists of soft and hard segments. The soft segments are primarily composed of polyols such as polyester / polyether, while the hard segments are composed of isocyanates, chain extenders, and crosslinking agents. By adjusting the types and proportions of soft and hard segments in the polyurethane polymer, different properties can be imparted to the polyurethane polishing pad. A higher proportion of hard segments can increase the modulus and hardness of the polyurethane polishing pad, enhancing its planarization ability. However, this can also lead to excessive phase separation between the hard and soft segments, and coarsening and aggregation of hard segments, resulting in reduced elongation at break and toughness, ultimately causing scratches and damage to the wafer surface. A higher proportion of soft segments can improve the toughness of the polyurethane polishing pad, making it less likely to damage the wafer. However, its modulus and wear resistance are insufficient, making it prone to creep deformation under pressure, weakening its planarization ability, and reducing polishing efficiency. Therefore, a single-formulation polyurethane material cannot achieve a balance between high planarization and low damage performance.
[0004] To improve the overall performance of polyurethane polishing pad materials, existing technologies typically employ methods such as polyurethane matrix molecular modification and the addition of reinforcing phases. Regarding polyurethane matrix modification, traditional chain extenders such as 1,4-butanediol are used to adjust the hard segment structure to enhance material strength. However, the hard segment structures formed by these chain extenders are well-defined and highly crystalline, often resulting in a significant loss of toughness along with increased strength. Furthermore, their effect on optimizing the microphase separation structure of hard segments is limited, failing to fundamentally improve the balance between strength and toughness. In addition, introducing modified inorganic nanoparticles into the polyurethane matrix as reinforcing phases for filling modification, relying on the load transfer and stress dissipation effects of nanoparticles, can improve the material's modulus and tensile strength. However, inorganic nanoparticles tend to have high hardness and rigidity, and when the filling amount is too high, they easily become stress concentration points, thereby reducing the material's elongation at break and toughness. Moreover, the polishing process is prone to producing wafer scratches.
[0005] In summary, to address the aforementioned problems with traditional chain extenders and inorganic nanoparticles in polyurethane materials, developing a high-strength polyurethane material for polishing pads is of great significance. Summary of the Invention
[0006] The purpose of this invention is to provide a high-strength polyurethane material for polishing pads and a method for preparing the same, so as to solve the problems mentioned in the background art.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] 1. A method for preparing a high-strength polyurethane material for polishing pads, comprising the following steps:
[0009] S1: Under a nitrogen atmosphere, N-methylmonoethanolamine and dimethyl carbonate are stirred and mixed evenly, and the mixture is heated to carry out pre-reaction and deep reaction in sequence to obtain a chain extender; polytetrahydrofuran ether diol, chain extender and diphenylmethane diisocyanate are mixed evenly and placed in a mold for curing to obtain a polyurethane matrix;
[0010] S2: Aramid nanofibers and silane coupling agent are added to an ethanol aqueous solution, stirred and dispersed evenly, and heated to react to obtain a reaction solution; tetraethyl orthosilicate is added to the reaction solution, heated to react, and after the reaction is completed, the mixture is washed with alcohol, washed with water, and vacuum dried to obtain modified aramid nanofibers;
[0011] S3: Thermoplastic polyurethane is dissolved in tetrahydrofuran, and modified aramid nanofibers are added under ultrasonic conditions and dispersed evenly to obtain a mixture; the mixture is added to deionized water, stirred evenly, filtered, washed, and vacuum dried to obtain the modified aramid nanofiber material;
[0012] S4: Polyurethane matrix, modified aramid nanofiber material, and thermoplastic polyurethane are mixed and molded, and then supercritical carbon dioxide is introduced for foaming treatment to obtain high-strength polyurethane material for polishing pads.
[0013] Further, in step S1, during the preparation of the chain extender, the molar ratio of N-methylmonoethanolamine to dimethyl carbonate is (3~3.1):1; the pre-reaction temperature is 80~85℃, the pre-reaction time is 5~6h; the deep reaction temperature is 150~160℃, and the deep reaction time is 8~10h.
[0014] Further, in step S1, during the preparation of the polyurethane matrix, the molecular weight of polytetrahydrofuran ether diol is 1000~2000 g / mol; the molar ratio of polytetrahydrofuran ether diol, chain extender, and diphenylmethane diisocyanate is 1:(1~1.02):(2~2.1); the curing temperature is 80~85℃, and the curing time is 20~24h.
[0015] Further, in step S2, during the preparation of the reaction solution: the diameter of the aramid nanofibers is 10~100nm, the silane coupling agent is one or a combination of γ-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane, the volume fraction of the ethanol aqueous solution is 90%~95%, the mass ratio of aramid nanofibers, silane coupling agent and ethanol aqueous solution is 1:(0.1~0.2):(8~9), the reaction temperature is 30~35℃, and the reaction time is 3~5h.
[0016] Furthermore, in step S2, during the preparation of modified aramid nanofibers: the mass ratio of tetraethyl orthosilicate to the reaction solution is 1:(95~100), the reaction temperature is 40~45℃, the reaction time is 4~5h, the vacuum drying temperature is 50~60℃, and the vacuum drying time is 10~12h.
[0017] Further, in step S3, during the preparation of the mixture, the mass ratio of thermoplastic polyurethane, tetrahydrofuran, and modified aramid nanofibers is 1:(10~15):(0.4~0.5), and the melt index of the thermoplastic polyurethane is 10~30 g / 10 min; during the preparation of the modified aramid nanofiber material, the mass ratio of the mixture to deionized water is 1:(10~15), the vacuum drying temperature is 50~60℃, and the vacuum drying time is 12~24 h.
[0018] Further, in step S4, the raw material components of the high-strength polyurethane material for the polishing pad are, by weight, 60-80 parts of polyurethane matrix, 5-15 parts of modified aramid nanofiber material, and 10-20 parts of thermoplastic polyurethane.
[0019] Furthermore, in step S4, the mixing and molding temperature is 160~180℃, the foaming treatment temperature is 120~140℃, the foaming treatment time is 1~2h, and the foaming treatment pressure is 10~12Mpa.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] 1. This invention prepares a chain extender using N-methylmonoethanolamine and dimethyl carbonate. Its molecular structure has abundant urethane groups, which can increase the hydrogen bond density and cohesive strength of the hard segments of polyurethane, thereby improving the tensile strength, hardness and wear resistance of polyurethane materials.
[0022] 2. This invention utilizes silane coupling agents to modify aramid nanofibers and incorporates them into polyurethane materials. This not only improves the problems of poor compatibility and weak interfacial bonding between aramid nanofibers and the polyurethane matrix, but also, since aramid nanofibers themselves possess both high strength and flexibility, when dispersed in the polyurethane matrix, uniform nanoscales are formed in localized areas under high strain. This can improve the strength and toughness of the polyurethane material through bridging and entanglement effects.
[0023] 3. The polyurethane material prepared by this invention has a tensile strength of up to 31.7 MPa and an elongation at break of up to 296%, which solves the problem of the imbalance between strength and toughness caused by the hard segment structure of traditional polyurethane materials. It is resistant to compression, has high polishing removal efficiency, and can be applied to polishing pads and other fields. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1: A method for preparing a high-strength polyurethane material for polishing pads: S1: Under a nitrogen atmosphere, 3 mol of N-methyl monoethanolamine and 1 mol of dimethyl carbonate were stirred and mixed evenly, and the mixture was heated to 80°C for pre-reaction for 6 hours, and then heated to 160°C for deep reaction for 8 hours. After the reaction, excess N-methyl monoethanolamine was removed by vacuum distillation to obtain a chain extender; 1 mol of polytetrahydrofuran ether diol with a molecular weight of 2000 g / mol, 1 mol of chain extender, and 2 mol of diphenylmethane diisocyanate were mixed evenly and placed in a mold, and cured at 80°C for 24 hours to obtain a polyurethane matrix;
[0026] S2: Add 5g of aramid nanofibers and 0.7g of γ-aminopropyltriethoxysilane to 45g of 95% ethanol aqueous solution, stir and disperse evenly, heat to 30℃ and react for 3h to obtain a reaction solution; add 0.5g of tetraethyl orthosilicate to the reaction solution, heat to 40℃ and react for 4h, wash the reaction product three times with ethanol and deionized water, and vacuum dry at 50℃ for 10h to obtain modified aramid nanofibers;
[0027] S3: Dissolve 10g of thermoplastic polyurethane with a melt index of 20g / 10min in 100g of tetrahydrofuran. Under ultrasonic conditions, add 5g of modified aramid nanofibers and disperse evenly to obtain a mixture. Add the mixture to 1200g of deionized water, stir evenly, filter, wash with ethanol and deionized water, and vacuum dry at 50℃ for 12h to obtain the modified aramid nanofiber material.
[0028] S4: 70g of polyurethane matrix, 10g of modified aramid nanofiber material and 20g of thermoplastic polyurethane are mixed and molded at 170℃, and then supercritical carbon dioxide is introduced for foaming treatment. The foaming treatment temperature is 130℃, the foaming treatment time is 1.5h and the foaming treatment pressure is 10Mpa to obtain high-strength polyurethane material for polishing pads.
[0029] Example 2: A method for preparing a high-strength polyurethane material for polishing pads: S1: Under a nitrogen atmosphere, 3 mol of N-methyl monoethanolamine and 1 mol of dimethyl carbonate were stirred and mixed evenly, and the mixture was heated to 80°C for pre-reaction for 6 hours, and then heated to 160°C for deep reaction for 8 hours. After the reaction, excess N-methyl monoethanolamine was removed by vacuum distillation to obtain a chain extender; 1 mol of polytetrahydrofuran ether diol with a molecular weight of 2000 g / mol, 1 mol of chain extender, and 2 mol of diphenylmethane diisocyanate were mixed evenly and placed in a mold, and cured at 80°C for 24 hours to obtain a polyurethane matrix;
[0030] S2: Add 5g of aramid nanofibers and 0.7g of γ-aminopropyltriethoxysilane to 45g of 95% ethanol aqueous solution, stir and disperse evenly, heat to 30℃ and react for 3h to obtain a reaction solution; add 0.5g of tetraethyl orthosilicate to the reaction solution, heat to 40℃ and react for 4h, wash the reaction product three times with ethanol and deionized water, and vacuum dry at 50℃ for 10h to obtain modified aramid nanofibers;
[0031] S3: Dissolve 10g of thermoplastic polyurethane with a melt index of 20g / 10min in 100g of tetrahydrofuran. Under ultrasonic conditions, add 5g of modified aramid nanofibers and disperse evenly to obtain a mixture. Add the mixture to 1200g of deionized water, stir evenly, filter, wash with ethanol and deionized water, and vacuum dry at 50℃ for 12h to obtain the modified aramid nanofiber material.
[0032] S4: Mix 80g of polyurethane matrix, 10g of modified aramid nanofiber material and 20g of thermoplastic polyurethane at 170℃ and then introduce supercritical carbon dioxide for foaming treatment. The foaming treatment temperature is 130℃, the foaming treatment time is 1.5h, and the foaming treatment pressure is 10Mpa to obtain high-strength polyurethane material for polishing pads.
[0033] Example 3: A method for preparing a high-strength polyurethane material for polishing pads: S1: Under a nitrogen atmosphere, 3 mol of N-methyl monoethanolamine and 1 mol of dimethyl carbonate were stirred and mixed evenly, and the mixture was heated to 80°C for pre-reaction for 6 hours, and then heated to 160°C for deep reaction for 8 hours. After the reaction, excess N-methyl monoethanolamine was removed by vacuum distillation to obtain a chain extender; 1 mol of polytetrahydrofuran ether diol with a molecular weight of 2000 g / mol, 1 mol of chain extender, and 2 mol of diphenylmethane diisocyanate were mixed evenly and placed in a mold, and cured at 80°C for 24 hours to obtain a polyurethane matrix;
[0034] S2: Add 5g of aramid nanofibers and 0.7g of γ-aminopropyltriethoxysilane to 45g of 95% ethanol aqueous solution, stir and disperse evenly, heat to 30℃ and react for 3h to obtain a reaction solution; add 0.5g of tetraethyl orthosilicate to the reaction solution, heat to 40℃ and react for 4h, wash the reaction product three times with ethanol and deionized water, and vacuum dry at 50℃ for 10h to obtain modified aramid nanofibers;
[0035] S3: Dissolve 10g of thermoplastic polyurethane with a melt index of 20g / 10min in 100g of tetrahydrofuran. Under ultrasonic conditions, add 5g of modified aramid nanofibers and disperse evenly to obtain a mixture. Add the mixture to 1200g of deionized water, stir evenly, filter, wash with ethanol and deionized water, and vacuum dry at 50℃ for 12h to obtain the modified aramid nanofiber material.
[0036] S4: 70g of polyurethane matrix, 15g of modified aramid nanofiber material and 20g of thermoplastic polyurethane are mixed and molded at 170℃, and then supercritical carbon dioxide is introduced for foaming treatment. The foaming treatment temperature is 130℃, the foaming treatment time is 1.5h and the foaming treatment pressure is 10Mpa to obtain high-strength polyurethane material for polishing pads.
[0037] Comparative Example 1: A method for preparing a polyurethane material: S1: 1 mol of polytetrahydrofuran ether diol with a molecular weight of 2000 g / mol, 1 mol of 1,4-butanediol and 2 mol of diphenylmethane diisocyanate are mixed evenly and placed in a mold and cured at 80°C for 24 h to obtain a polyurethane matrix;
[0038] S2: Mix 80g of polyurethane matrix and 20g of thermoplastic polyurethane at 170℃, then introduce supercritical carbon dioxide for foaming treatment. The foaming treatment temperature is 130℃, the foaming treatment time is 1.5h, and the foaming treatment pressure is 10Mpa to obtain polyurethane material.
[0039] Comparative Example 2: A method for preparing a polyurethane material: S1: Under a nitrogen atmosphere, 3 mol of N-methyl monoethanolamine and 1 mol of dimethyl carbonate were stirred and mixed evenly, and the mixture was heated to 80℃ for pre-reaction for 6 h, and then heated to 160℃ for deep reaction for 8 h. After the reaction, excess N-methyl monoethanolamine was removed by vacuum distillation to obtain a chain extender; 1 mol of polytetrahydrofuran ether diol with a molecular weight of 2000 g / mol, 1 mol of chain extender, and 2 mol of diphenylmethane diisocyanate were mixed evenly and placed in a mold, and cured at 80℃ for 24 h to obtain a polyurethane matrix;
[0040] S2: Mix 80g of polyurethane matrix and 20g of thermoplastic polyurethane at 170℃, then introduce supercritical carbon dioxide for foaming treatment. The foaming treatment temperature is 130℃, the foaming treatment time is 1.5h, and the foaming treatment pressure is 10Mpa to obtain polyurethane material.
[0041] Comparative Example 3: A method for preparing a polyurethane material: S1: 1 mol of polytetrahydrofuran ether diol with a molecular weight of 2000 g / mol, 1 mol of 1,4-butanediol and 2 mol of diphenylmethane diisocyanate are mixed evenly and placed in a mold and cured at 80°C for 24 h to obtain a polyurethane matrix;
[0042] S2: Add 5g of aramid nanofibers and 0.7g of γ-aminopropyltriethoxysilane to 45g of 95% ethanol aqueous solution, stir and disperse evenly, heat to 30℃ and react for 3h to obtain a reaction solution; add 0.5g of tetraethyl orthosilicate to the reaction solution, heat to 40℃ and react for 4h, wash the reaction product three times with ethanol and deionized water, and vacuum dry at 50℃ for 10h to obtain modified aramid nanofibers;
[0043] S3: Dissolve 10g of thermoplastic polyurethane with a melt index of 20g / 10min in 100g of tetrahydrofuran. Under ultrasonic conditions, add 5g of modified aramid nanofibers and disperse evenly to obtain a mixture. Add the mixture to 1200g of deionized water, stir evenly, filter, wash with ethanol and deionized water, and vacuum dry at 50℃ for 12h to obtain the modified aramid nanofiber material.
[0044] S4: 70g of polyurethane matrix, 10g of modified aramid nanofiber material and 20g of thermoplastic polyurethane are mixed and molded at 170℃, and then supercritical carbon dioxide is introduced for foaming treatment. The foaming treatment temperature is 130℃, the foaming treatment time is 1.5h and the foaming treatment pressure is 10Mpa to obtain polyurethane material.
[0045] Comparative Example 4: A method for preparing a polyurethane material: S1: Under a nitrogen atmosphere, 3 mol of N-methyl monoethanolamine and 1 mol of dimethyl carbonate were stirred and mixed evenly, and the mixture was heated to 80℃ for pre-reaction for 6 h, and then heated to 160℃ for deep reaction for 8 h. After the reaction was completed, excess N-methyl monoethanolamine was removed by vacuum distillation to obtain a chain extender; 1 mol of polytetrahydrofuran ether diol with a molecular weight of 2000 g / mol, 1 mol of chain extender, and 2 mol of diphenylmethane diisocyanate were mixed evenly and placed in a mold, and cured at 80℃ for 24 h to obtain a polyurethane matrix;
[0046] S2: 5g of cerium dioxide nanoparticles with an average particle size of 100nm and 0.7g of γ-aminopropyltriethoxysilane were added to 45g of 95% ethanol aqueous solution. The mixture was stirred and dispersed evenly, and the temperature was raised to 30℃ for 3h to obtain a reaction solution. 0.5g of tetraethyl orthosilicate was added to the reaction solution, and the temperature was raised to 40℃ for 4h. The reaction product was washed three times with ethanol and deionized water, and then vacuum dried at 50℃ for 10h to obtain modified cerium dioxide nanoparticles.
[0047] S3: Dissolve 10g of thermoplastic polyurethane with a melt index of 20g / 10min in 100g of tetrahydrofuran. Under ultrasonic conditions, add 5g of modified cerium dioxide nanoparticles and disperse evenly to obtain a mixture. Add the mixture to 1200g of deionized water, stir evenly, filter, wash with ethanol and deionized water, and vacuum dry at 50℃ for 12h to obtain modified cerium dioxide nanomaterials.
[0048] S4: 70g of polyurethane matrix, 10g of modified cerium dioxide nanomaterials and 20g of thermoplastic polyurethane are mixed and molded at 170℃, and then supercritical carbon dioxide is introduced for foaming treatment. The foaming treatment temperature is 130℃, the foaming treatment time is 1.5h and the foaming treatment pressure is 10Mpa to obtain polyurethane material.
[0049] Performance testing of high-strength polyurethane material for polishing pads:
[0050] Tensile strength / elongation at break: The tensile strength and elongation at break of the polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested according to the requirements of GB / T528-2009.
[0051] Abrasion resistance: The abrasion of the polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-4 was tested in a Taber abrasion tester according to ASTM D4060 standard.
[0052] Shore hardness: The Shore hardness of the polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-4 was measured according to the requirements of GB / T531-2008.
[0053] Compression strength test: The polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-4 were made into 30mm×30mm×30mm cubes. The samples were compressed by 6mm using a universal testing machine at a compression speed of 3mm / min and a compression ratio of 20%.
[0054] Polishing performance testing: The polyurethane materials prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to polishing performance testing. The workpiece was glass with a diameter of 100 mm and a thickness of 0.5 mm. The abrasive was silica. The polishing fluid flow rate was 20 mL / min, the polishing head speed was 40 rpm, the polishing disc speed was 40 rpm, and the polishing time was 30 min. The material removal rate (MRR) was calculated.
[0055]
[0056] In the formula, Δm is the polishing quality difference, ρ is the glass density, r is the workpiece radius, and t is the polishing time.
[0057] The experimental results are shown in Table 1 below.
[0058] Table 1. Performance Test Data of High-Strength Polyurethane Material for Polishing Pads
[0059] Example 1 29.2 301 40 0.22 16.3 146 Example 2 31.7 296 43 0.19 17.7 151 Example 3 30.6 312 41 0.21 17.1 148 Comparative Example 1 16.9 244 22 0.48 6.8 73 Comparative Example 2 26.5 233 31 0.33 14.2 105 Comparative Example 3 20.6 324 29 0.35 10.5 93 Comparative Example 4 29.4 175 48 0.23 17.9 144
[0060] Conclusion: This invention improves the tensile strength and wear resistance of polyurethane materials through the prepared chain extender, and further enhances the strength and toughness of polyurethane materials by compounding with modified aramid nanofibers. The prepared polyurethane material has a tensile strength of up to 31.7 MPa and an elongation at break of up to 296%, which solves the problem of the imbalance between strength and toughness caused by the hard segment structure of traditional polyurethane materials. It is also resistant to compression and has high polishing removal efficiency, and can be applied to polishing pads and other fields.
[0061] Comparative Example 1 used 1,4-butanediol as a chain extender and did not add any nano-reinforcing agents. The polyurethane material had low tensile strength and hardness, was easily worn, easily deformed under compression, and had a low polishing removal rate.
[0062] In Comparative Example 2, no modified aramid nanofibers were added. The improvement in tensile strength and hardness of the polyurethane material was achieved by chain extenders, which was significantly weaker than that in the example and also weakened the toughness of the material.
[0063] In Comparative Example 3, 1,4-butanediol was used as a chain extender. The improvement in tensile strength, elongation at break, and hardness was achieved by modified aramid nanofibers, but the effect was significantly weaker than that of the example. The wear of the polyurethane material was too large, and the polishing removal rate was insufficient.
[0064] In Comparative Example 4, modified cerium dioxide nanoparticles were used as a reinforcing agent, which improved the tensile strength, hardness, and compressive strength of the polyurethane material. However, the toughness of the material was significantly reduced, which easily caused scratches and damage to the wafer surface.
[0065] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A method for preparing a high-strength polyurethane material for polishing pads, characterized in that: Includes the following steps: S1: Under a nitrogen atmosphere, N-methylmonoethanolamine and dimethyl carbonate are stirred and mixed evenly, and the mixture is heated to carry out pre-reaction and deep reaction in sequence to obtain a chain extender; polytetrahydrofuran ether diol, chain extender and diphenylmethane diisocyanate are mixed evenly and placed in a mold for curing to obtain a polyurethane matrix; S2: Aramid nanofibers and silane coupling agent are added to an ethanol aqueous solution, stirred and dispersed evenly, and heated to react to obtain a reaction solution; tetraethyl orthosilicate is added to the reaction solution, heated to react, and after the reaction is completed, the mixture is washed with alcohol, washed with water, and vacuum dried to obtain modified aramid nanofibers; S3: Thermoplastic polyurethane is dissolved in tetrahydrofuran, and modified aramid nanofibers are added under ultrasonic conditions and dispersed evenly to obtain a mixture; the mixture is added to deionized water, stirred evenly, filtered, washed, and vacuum dried to obtain the modified aramid nanofiber material; S4: Polyurethane matrix, modified aramid nanofiber material, and thermoplastic polyurethane are mixed and molded, and then supercritical carbon dioxide is introduced for foaming treatment to obtain high-strength polyurethane material for polishing pads.
2. The method for preparing a high-strength polyurethane material for polishing pads according to claim 1, characterized in that: In step S1, during the preparation of the chain extender, the molar ratio of N-methylmonoethanolamine to dimethyl carbonate is (3~3.1):1; the pre-reaction temperature is 80~85℃, the pre-reaction time is 5~6h; the deep reaction temperature is 150~160℃, and the deep reaction time is 8~10h.
3. The method for preparing a high-strength polyurethane material for polishing pads according to claim 1, characterized in that: In step S1, during the preparation of the polyurethane matrix, the molecular weight of polytetrahydrofuran ether diol is 1000~2000 g / mol; the molar ratio of polytetrahydrofuran ether diol, chain extender, and diphenylmethane diisocyanate is 1:(1~1.02):(2~2.1); the curing temperature is 80~85℃, and the curing time is 20~24h.
4. The method for preparing a high-strength polyurethane material for polishing pads according to claim 1, characterized in that: In step S2, during the preparation of the reaction solution: the diameter of the aramid nanofibers is 10~100nm, the silane coupling agent is one or a combination of γ-aminopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane, the volume fraction of the ethanol aqueous solution is 90%~95%, and the mass ratio of aramid nanofibers, silane coupling agent and ethanol aqueous solution is 1:(0.1~0.2):(8~9); the reaction temperature is 30~35℃, and the reaction time is 3~5h.
5. The method for preparing a high-strength polyurethane material for polishing pads according to claim 1, characterized in that: In step S2, during the preparation of modified aramid nanofibers: the mass ratio of tetraethyl orthosilicate to the reaction solution is 1:(95~100), the reaction temperature is 40~45℃, the reaction time is 4~5h, the vacuum drying temperature is 50~60℃, and the vacuum drying time is 10~12h.
6. The method for preparing a high-strength polyurethane material for polishing pads according to claim 1, characterized in that: In step S3, during the preparation of the mixture, the mass ratio of thermoplastic polyurethane, tetrahydrofuran, and modified aramid nanofibers is 1:(10~15):(0.4~0.5), and the melt index of thermoplastic polyurethane is 10~30 g / 10 min; during the preparation of modified aramid nanofiber materials, the mass ratio of the mixture to deionized water is 1:(10~15), the vacuum drying temperature is 50~60℃, and the vacuum drying time is 12~24 h.
7. The method for preparing a high-strength polyurethane material for polishing pads according to claim 1, characterized in that: In step S4, the raw material components of the high-strength polyurethane material for the polishing pad are, by weight, 60-80 parts of polyurethane matrix, 5-15 parts of modified aramid nanofiber material, and 10-20 parts of thermoplastic polyurethane.
8. The method for preparing a high-strength polyurethane material for polishing pads according to claim 1, characterized in that: In step S4, the mixing and molding temperature is 160~180℃, the foaming treatment temperature is 120~140℃, the foaming treatment time is 1~2h, and the foaming treatment pressure is 10~12Mpa.
9. The high-strength polyurethane material for polishing pads prepared by the method for preparing a high-strength polyurethane material for polishing pads according to any one of claims 1 to 8.